Genetic Polymorphism of Toll-Like Receptor 4 ASP299GLY Gene Polymorphism in Children with Helicobacter pylori Infection - O.Ye. Abaturov; O.M. Gerasymenko; O.A. Shlykova; I.P. Kaidashev (Zaslavsky O.Yu., 2013)
The objective of the study was to determine the characteristics of H.pylori infection in children with Toll-like receptor 4 (TLR4) ASP299GLY gene polymorphism. Methods. 31 children aged 9 to 17 years with chronic gastroduodenal pathology were observed. The control group included 95 healthy individuals. Results. Among children with chronic gastroduodenal pathology, 16.13 % had heterozygous genotype Asp/Gly, which is higher than in the control group (P = 0.01). It was shown that in H.pylori positive children the frequency of the heterozygous genotype Asp/Gly was higher than in H. pylori negative patients (17.4 and 12.5 %, respectively, OR = 1.48; P = 0.75). Among H.pylori positive children heterozygous genotype Asp/Gly was detected more frequently in children infected with СagA-positive strains of H.pylori, compared to patients with СagA-negative status (P > 0.5). It is proved that in children with TLR4 ASP299GLY gene polymorphism a decrease in the expression of TLR4 in biopsy sample of the gastric mucosa and water-soluble sCD14 levels was observed, together with prominent inflammatory mucosal changes (Pu < 0.05). Conclusion. Among children with chronic inflammatory gastroduodenal diseases, genotype Asp/Gly SNP Asp299Gly of the gene TLR4 is observed significantly higher than in healthy population. Presence of genotype Asp/Gly in children predisposes to contamination with H.pylori.